Kinetics study of copper (Cu) and chromium (Cr) adsorption using green mussel shells (Perna viridis) adsorbent - Febi Indah Fajarwati; Asfiya Mahanani; Mai Anugrahwati (Jurnal Pijar Mipa, 2023)
Research has been carried out on making green mussel shell adsorbents to absorb Cu and Cr metals. The study of making green mussel shell adsorbents was carried out by thermal activation using a furnace. The results of the activated adsorbent were characterized using FTIR and SEM-EDX. Furthermore, the adsorbent was used to absorb Cu and Cr metal by using several variations, namely variations in the temperature of the adsorbent activation, adsorbent weight, pH, and contact time, and knowing the kinetic model by determining the reaction order. The results obtained from the characterization of green mussel shells contain elements of Ca, about 67.56% at an activation temperature of 500 °C and 67.34% at an activation temperature of 900 °C. The optimum conditions for Cu metal adsorption by green shell adsorbent were obtained at an activation temperature of 500 °C, using an adsorbent of 1 gram under pH 10 and a contact time of 40 minutes. Whereas for Cr metal absorption, the activation temperature was 900 °C, the mass used was 1.5 grams with pH 7 and the contact time was 40 minutes. The adsorption kinetics model of green mussel shells adsorbent on Cu and Cr metals followed pseudo-second-order.